Active and passive biomonitoring of trace elements, polycyclic aromatic hydrocarbons, and polychlorinated biphenyls in small Mediterranean harbours. (February 2023) - Castrec, Justine; Pillet, Marion; Receveur, Justine; Fontaine, Quentin; Le Floch, Stéphane; Churlaud, Carine; Lejeune, Pierre; Gobert, Sylvie; Thomas, Hélène; Marengo, Michel
Abstract: Pollution particularly affects coastal ecosystems due to their proximity to anthropic sources. Among those environments, harbours are subjected to marine traffic but also to accidental and chronic pollution. These areas are thus exposed to complex mixtures of contaminants such as trace elements and organic contaminants which can impact marine species, habitats, and ecosystem services. The monitoring of these compounds is thus a crucial issue for assessment of environmental health. In this context, the aim of the present work was to evaluate the chemical contamination of harbours in Corsica (NW Mediterranean) by measuring the bioaccumulation of trace elements, polycyclic aromatic hydrocarbons, and polychlorinated biphenyls in mussels, limpets, and sea cucumbers. The human health risks associated with seafood consumption were also assessed. Results reveal a relatively low contamination in the Corsican harbours studied compared to larger Mediterranean ports and suggest that the potential health risk for consumers eating seafood is low. Highlights: Trace elements, PAHs, and PCBs were monitored in Corsican harbours. The bioindicators considered were native limpets, sea cucumbers, and caged mussels. Heavy metals, PCBs and PAHs were detected in seafood samples. The contaminant levels were below their maximum allowable concentrations. The study suggests low contamination compared to other Mediterranean ports.